Visible-light-mediated sulfonylation of anilines with sulfonyl fluorides - Li, Xin-Qing; Liao, Qian-Qian; Lai, Jun; Liao, Yuan-Yue (Frontiers in Chemistry, 2023)
A visible-light-mediated sulfonylation of aniline with using sulfonyl fluoride as modifiable and stable sulfonylation reagent is described. A variety of substituted sulfonylanilines were synthesized under mild reaction conditions with moderate to good efficiency. The example of late-stage sulfonylation highlighted the advantage of using sulfonyl fluoride as sulfonylation reagent. And the crucial influence of counterion in photocatalyst observed in this system would inspire further research on the photochemistry.